Application of DNA barcode for the genetic analysis and identifying a May nuoc mo species in Quang Nam Province, Central Vietnam - HUYNH KIM HIEU; NGUYEN VAN MINH; NGUYEN VAN LOI; HO THANH HA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hieu HK, Minh NV, Loi NV, Ha HT. 2024. Application of DNA barcode for the genetic analysis and identifying a May nuoc mo species in Quang Nam Province, Central Vietnam. Biodiversitas 25: 3299-3308. Precise identification in Calamus, the genus in the subfamily Calamoideae (Arecaceae), is challenging due to taxonomic complexities. This study aimed to discriminate and identify the 23 May nuoc mo samples collected from Quang Nam, Vietnam using four barcoding regions (rbcL, matK, psbA-trnH, and ITS nrDNA) and combined with morphological characters. DNA sequence data from those regions were analyzed using distance, tree, and similarity-based statistical methods. All region sequences presented no variable sites, except for rbcL gene region with a low rate of nucleotide differences of 0.270%. The results of the 23 May nuoc mo samples were highly similar from 99.73 to 100% to Calamus sp. N_XT142 (ON248649.1 and MK692404.1) and no gene regions were proposed as barcodes for species identification in this study. All samples shared certain morphological characteristics, including leaflets arranged regularly but with gaps; petioles with yellow spine groups; and leaf sheaths with hairs, densely arranged with brown, triangular, and flattened spines, and interspersed among many short, and black spines. Based on these results, we recommend using some other gene regions (rpoC, and rpoB)) in species identification to shed more light on these May nuoc mo samples with subsequent studies.